Financial Performance Evaluation Using Profitability and Liquidity Ratio Analysis - Hasidi, Mirza Hapsari; Baheri, Jusbair; Hajar, Khaerunnisa Ibnu (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
A company's financial performance is an important indicator used to assess the financial health and operational efficiency of a business entity. In the context of PT Rig Tenders Indonesia Tbk, the consolidated financial statements as of March 31, 2024 showed an increase in current assets to IDR 330.44 billion from IDR 263.97 billion in the previous period. Although the company has recorded an increase in current assets and net profit, unstable global economic conditions can cause uncertainty in revenue and operating costs. This study uses a quantitative research design with a descriptive approach to evaluate the financial performance of PT Rig Tenders Indonesia Tbk through profitability and liquidity ratio analysis. The results of the study show that PT Rig Tenders Indonesia Tbk has good financial performance with high liquidity, significant profitability, and effective asset management. The company shows a strong ability to meet short-term obligations and generate profits from its assets and equity. A holistic and sustainable evaluation of financial performance is essential to maintain the stability and growth of the company in the future. The findings of this study provide important contributions both theoretically and practically in the field of financial management. Theoretically, this study enriches the literature on financial ratio analysis with a focus on the maritime industry. In practice, these findings offer solutions for companies in managing risk and improving operational efficiency through better asset management strategies and investment diversification. The limitation of this study lies in the use of financial data in one period that may not reflect long-term dynamics. For future research, it is recommended to examine financial data in a longer period and consider other external factors such as regulatory changes and global market conditions.